Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Sapphire Sky Hotel BSD Kota Tangerang Selatan - Trida Anggara; Theobaldus Boro Tura (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to analyze the effect of leadership style and organizational culture on employee performance at Sapphire Sky Hotel BSD, South Tangerang City. The method used in this research is quantitative with an associative approach. The sample used was 63 respondents who were taken with saturated sampling technique. Data collection techniques were carried out through distributing questionnaires, and data analysis was carried out using SPSS version 29 by testing validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test, and F test. The results showed that partially, leadership style (X₁) had a positive and significant effect on employee performance with a tcount value of 3.902> t table 1.998 and a significance of 0.000 < 0.05. Organizational culture (X₂) also has a positive and significant effect on employee performance with a tcount value of 2.406 > t table 1.998 and a significance of 0.019 < 0.05. Simultaneously, both variables have a significant effect on employee performance with an Fcount value of 26.042> Ftable 3.15 and a significance of 0.000 <0.05. The coefficient of determination (R²) value is 46.6%, which means that employee performance is influenced by leadership style and organizational culture, while the remaining 53.4% is influenced by other variables not examined in this study.